6a-1r=6

Simple and best practice solution for 6a-1r=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a-1r=6 equation:


Simplifying
6a + -1r = 6

Solving
6a + -1r = 6

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add 'r' to each side of the equation.
6a + -1r + r = 6 + r

Combine like terms: -1r + r = 0
6a + 0 = 6 + r
6a = 6 + r

Divide each side by '6'.
a = 1 + 0.1666666667r

Simplifying
a = 1 + 0.1666666667r

See similar equations:

| 10-w=285 | | 3y+1=5.2 | | -70+7=63 | | 4[d+f]= | | 0.625x-2=-12 | | 4/3(x-3)=8 | | 5x+7x-34=85-5x | | 8x+7=-3x-1 | | 2sin^2x-sinx+1=0 | | 9(z-913)=315 | | 21-5h=h+6 | | 13(-6x)+15=375 | | 14(t-910)=476 | | -5p+3=43 | | .80x+.20(70)=.70(70+x) | | .80x+.25(70)=.70(70+x) | | 4(s-859)=344 | | (x-2)=12(y-3) | | 2x+76=170 | | X+2y-7=6 | | (R/3)-4=11 | | x+2+x+4+x=180 | | 5x/3-2=13 | | 4(2-3b)=6b-4(b+5) | | 4(3x-2)-3=4(x-3)+33 | | 8m+20=2m | | 8(z-927)=256 | | 24a=6a*4 | | 300=x+75 | | 2y-7/y | | Y-7=14.1 | | 240=x-60 |

Equations solver categories